Causes and Effects of Building Collapse in Nigeria - Ibrahim, Tajudeen Akogun; Suleiman, Bolaji; Bello, Nurudeen Akinsola (NIU Journal of Social Sciences, 2019)
The incidence of building collapse in Nigeria has taken an alarming dimension owing to the frequency of its occurrence and the impacts it has on the nation. It became incessant that a month could hardly passed by without a case of building collapse, with its attendant gruesome effects that could not be easily forgotten by its victims. The study examines the causes and effects of building collapse in Nigeria with a view to proffering pragmatic solutions. The bulk of the data used in this paper was derived from archival sources and content analysis of different research findings in relation to building collapse in major urban centres in Nigeria. A sample size of 200 landed professionals (20 each from 10 categories of landed professionals) selected randomly were surveyed through administration of questionnaire.  A response rate of 94% was obtained. Data gathered were analysed by frequency distribution, percentage and relative importance indices. Findings of the study revealed that most of the causes of building collapse have been attributed to poor workmanship, bad design, substandard materials, non-involvement of registered professionals and use of incompetent contractors. The study also revealed that its multidimensional effects include economic, social, psychological and environmental impacts. The specific effects revealed are loss of life, properties, income; pollution, and phobia. The study recommended that relevant professionals should be involved in project execution, supervision and monitoring from inception to completion; government must ensure availability of good construction materials at affordable costs and prosecution of dealers in poor quality construction materials and erring contractors. Keywords: Abeokuta, building collapse, building construction, construction industry, Nigeria